Qualitative and quantitative contrast-enhanced ultrasonography for the characterisation of non-palpable testicular tumours. Issue 3 (March 2018) - Luzurier, A.; Maxwell, F.; Correas, J.M.; Benoit, G.; Izard, V.; Ferlicot, S.; Teglas, J.P.; Bellin, M.F.; Rocher, L.
Abstract : Aim: To assess the diagnostic performance of conventional ultrasound (US) and contrast-enhanced ultrasonography (CEUS) in the differential diagnosis of non-palpable intratesticular tumours. Materials and methods: The local ethics review board approved the protocol, and all of the patients provided written informed consent. Between December 2011 and February 2014, men with non-palpable testicular tumours and normal tumour markers who were referred for surgery were included. The tumours were analysed by conventional US, including B-mode and colour Doppler US (CDUS) as well as by CEUS. Morphological aspects and qualitative and quantitative CEUS criteria, based on visual enhancement and time–intensity curves, were assessed for each lesion. Results: Forty patients were ultimately included. Based on histopathological results, the tumours were classified into three groups: benign tumours ( n= 16), malignant tumours ( n= 15), and burned-out tumours ( n= 9). In B-mode, the morphological aspects were significantly different between benign and malignant tumours ( p -values from 0.0002 to 0.008). Qualitative and quantitative analyses of the CEUS images revealed that burned-out tumours exhibited significantly less enhancement than malignant and benign tumours: in burned-out tumours, time–intensity curves were flat, whereas in both benign and malignant tumours the curves had a bell-shaped pattern. All intensity parameters were lower for burned-out tumours compared to benign and malignant tumours ( p -value from 0.0001 to 0.026). Both benign and malignant tumours enhanced strongly, however, and no significant difference between the two was noted ( p -value from 0.0721 to 0.0953). Conclusion: Unlike conventional US, which enable benign lesions to be differentiated from malignant or burned-out tumours, CEUS failed to enabled differentiation between benign lesions and malignant vascularised testicular tumours. CEUS appears to have the potential, however, to differentiate burned-out tumours from vascularised testicular tumours. Highlights: Unenhanced US identified features that allowed benign tumours to be differentiate from malignant and burned-out tumours. CEUS may be a good technique to differentiate burned-out tumours from benign and active malignant tumours. However, CEUS didn't provide arguments to differentiate benign testicular tumours from malignant testicular tumours.